RANCANG BANGUN SISTEM PELAPORAN PENDAPATAN HARIAN DENGAN SMS GATEWAY DAN MONITORING HASIL BERBASIS WEB PADA PERUSAHAAN PENGISIAN BAN NITROGEN - Malikus Sumadyo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2009)
PT Insight Strategic Partner is a company that manages the filling tires with nitrogen gas which has an office in Bekasi and manage dozens of tire filling stations at Jabodetabek even Bandung. Every day each filling tire station operators report daily attendance and revenue to the central office. On each day of field supervisors and investors are also able to monitor the progression of earnings results on the web. This system was created in order to receive a daily reporting of attendance and revenues at each station filling tires using the SMS and sends back a reply to the sender. And the system will also transmit data reporting daily attendance and revenueare on the web. The system is built with PHP and MySQL database running on localhost on a localserver, and also running on the server hosting. SMS from the service station is received by the GSM modem connected to the local server then local server will send back an answer to the operator. At the same time, using XML, the local server will send the input to the hosting server, so it can be Shown on the web.